2003
DOI: 10.1046/j.1365-2249.2003.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric determination of glucocorticoid receptor (GCR) expression in lymphocyte subpopulations: lower quantity of GCR in patients with post-traumatic stress disorder (PTSD)

Abstract: SUMMARYAssessment of the intracellular glucocorticoid receptor (GCR) level may be useful in monitoring functional disturbances of the hypothalamic-pituitary-adrenocortical axis or effects of prolonged steroid therapy. Cytosolic ligand binding assays have recently been supplemented by flow cytometric determination of receptor expression in individual cells. A method based on multiparametric analysis of whole blood by simultaneous labelling of intracellular GCRs and surface markers of lymphocyte subsets is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…In addition, changes in the regulation of the HPA axis could be followed. Gotovac et al 54 have shown in their longitudinal study on a similar group of PTSD patients initially increased cortisol concentrations and natural killer cell cytotoxicity. However, cortisol concentrations decreased with the passing of time after a traumatic experience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, changes in the regulation of the HPA axis could be followed. Gotovac et al 54 have shown in their longitudinal study on a similar group of PTSD patients initially increased cortisol concentrations and natural killer cell cytotoxicity. However, cortisol concentrations decreased with the passing of time after a traumatic experience.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Flow cytometric determination of GR expression in lymphocyte subpopulations even revealed a lower GR expression in all lymphocyte subsets from PTSD patients compared to healthy individuals. 33 To get an indication of GR function in the immune system, the capacity of glucocorticoids to inhibit immune responses in vitro 32,34 as well as in vivo dexamethasone (DEX)-induced changes in leukocyte GR binding 30,31 have been measured in PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD has been associated with low plasma cortisol and an increased sensitivity to glucocorticoids (Coupland et al, 2003;Goenjian et al, 1996;Gotovac et al, 2003;Rohleder et al, 2004;Stein et al, 1997b;Yehuda et al, 1995Yehuda et al, , 2004a. Changes in trace eyeblink conditioning following a pharmacological challenge with hydrocortisone could help evaluate glucocorticoid sensitivity of focal brain regions such as the hippocampus in PTSD.…”
Section: Introductionmentioning
confidence: 99%